ANALYSIS OF DELAY FACTORS IN THE CONSTRUCTION PROJECT OF THE PROMOTION CENTER BUILDING AND BATIK DERIVATIVE PRODUCTION BUILDING IN PAMEKASAN - Fatoni, Ahmad; Zabadi, Fairus; Saifuddin, Muhammad (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
The construction of the Promotion Center Building and Written Batik Derivative Production Building is a development project with service provider PT. Hariz Three Sons. Tree Analysis (FTA) to determine the causes and impact of risk failure and Critical Path Method (CPM) to determine the extent to which work experiences a critical path. The most dominant causal factors are factors caused by external factors, namely in the form of very high rainfall intensity in one month and unilateral blockades by village officials. The causal factor caused by the owner is the delay in submitting design changes to the field where the design is very important as a development guide. Meanwhile, delays caused by implementers are inappropriate duration determinations that result in work productivity not being properly controlled. Floor work and wall ornaments this work on the last day of the contract only produced 1.286% of the total 17.50%, which means there was a deviation of -16.211%. Floor work and wall ornaments have several work items including Install UK Polished Ceramic Floors. 60 x 60 cm, Install KM/WC Color Ceramic Floor 20 x 20 cm, Install Color Ceramic Wall 20 x 40 cm, Install 1 m ceramic plinth measuring 5 cm x 20 cm, Install 1 m2 Cutting Plate 5mm Thick Batik Motif + frame and Lettering Jobs. Keywords: Project Delay Factors; Fault Tree Analysis (FTA); Critical Path Method (CPM).